Evaluasi Penggantian Tanah dan Injeksi Grouting Semen Terhadap Penurunan Tanah - Arief Andriansyah; Lusmeilia Afriani; Dyah Indriana Kusumastuti; Endro P. Wahono (Journal of Sustainability Science and Technology, 2021)
This paper discusses the process of original soil stabilization in Trans Sumatra Bakauheni-Terbanggi Besar Toll Road Project Package 2 Sidomulyo-Kotabaru. The soil replacement process was conducted at approximately 24 kilometres along the toll’s main road. The original soil bearing capacity analysis stage was by performing a Dynamic Cone Penetrometer (DCP) and Sondir test to analyze the deep of hard soil. A soil replacement was carried out to replace the original soil with soil that has appropriate specification. the piling up process was conducted in stages, which has Sandstone in such of the layer. The research done about the landfill sample was retaken and collected at 68 points. The stockpile soil samples collection was then followed by the analysis which was conducted in the laboratory to find the soil bearing capacity. There are 4 types of bearing capacity parameters analyzed, namely specific gravity, water content, aggregate analysis (Sieve Analysis), and consistency limit (Atterberg Limit). Referring to it, then there was the classification of soil types according to AASHTO M145 & Casagrande Soil Classification System. A point that has settlement after soil replacement is STA 52+000. So, there need to add soil stabilization, that is cement grout injection. Researchers analyzed the soil settlement by interpretation method. Results showed that soil replacement and cement grout injection could decrease a soil settlement by about 15.07 cm to become 0.93 cm.